Dividend policy, investment opportunity set, free cash flow, and company performance: Indonesian’s agricultural sector - Choiri Chosiah; Budi Purwanto; Wita Juwita Ermawati (University of Merdeka Malang, 2019)
Dividends are a tool that can be an essential source of information for investors or other stakeholders as it contains information that can provide a signal about the company's prospects (dividend signaling theory). This study aims to examine the effect of dividend policy on company performance through moderation of investment opportunity set (IOS) and free cash flow (FCF) and examine the effect of the application of corporate governance on dividend policy and company performance. Based on purposive sampling technique obtained a sample of 71 companies that meet the criteria. The study was conducted using panel data regression method. The results showed that dividend policy had a significant negative effect on company performance in the following year. IOS has a positive and insignificant effect on company performance, while FCF has a positive and significant effect on company performance. IOS variable is able to moderate the relationship of dividend policy on company performance in the following year, while FCF is not able to moderate the influence of dividend policy on company performance in the following year. In addition, the corporate governance mechanism has an insignificant effect on dividend policy which shows that the corporate governance mechanism is still not effective in increasing the number of dividends paid to shareholders.JEL Classification: D13, I31, J22DOI: https://doi.org/10.26905/jkdp.v23i3.2517